SMEs in services trade: A GATS perspective - Rudolf Adlung; Marta Soprana (Intereconomics, 2013)
Unlike traditional (goods-only) trade agreements, the scope of the General Agreement on Trade in Services extends beyond the treatment of products (services) to cover that of suppliers as well. The trade interests of particular groups of suppliers, including SMEs, can thus be addressed directly under the Agreement. This paper provides an overview of potentially relevant policies and policy disciplines. It also seeks to identify the scope for further initiatives, from fostering compliance with existing transparency obligations to advancing the Agreement's liberalisation and rule-making mandates from an SME perspective.
Keywords: 330; GATS; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; KMU; Welt